Pengaruh Media Papan Statistika Terhadap Hasil Belajar Siswa Pada Materi Pengolahan Data Di Kelas V SD Negeri Monsinget Aceh Besar - Puspita, Dian; Linda, Vitoria; Mislinawati, Mislinawati (Universitas Syiah Kuala, 2023)
The purpose of this study was to determine the effect of statistical board media on student learning outcomes in data processing material in class V SD Negeri Monsinget Aceh Besar. The approach taken is the quantitative experimental method with the type of research Pre-Experimental Designs with the One-Group Pretest-Posttest Design. Place of research at SD Negeri Mosinget Aceh Besar. Samples were taken from all 22 students of class V at SD Negeri Monsinget Aceh Besar. The data collection technique used was a test, while the data analysis technique used hypothesis testing with the Paired Samples Test t-test with the help of IBM SPSS Statistics Version 26 For Windows. The result of testing the hypothesis with the Paired Samples Test statistical t-test obtained a significance value (2-tailed) of 0,000 0,05. Where the decision-making criteria are Ha accepted or Ho rejected. So, it can be concluded that there is an influence of statistical board media on student learning outcomes in data processing material in class V SD Negeri Monsinget Aceh Besar.